The complexation of Cm(III) with oxalate in aqueous solution at T = 20-90 °C: a combined TRLFS and quantum chemical study - Skerencak-Frech, Andrej; Maiwald, Martin M.; Trumm, Michael; Fröhlich, Daniel R.; Panak, Petra (Inorganic chemistry, 2015)
The complexation of Cm(III) with oxalate is studied in aqueous solution as a function of the ligand concentration, the ionic strength (NaCl), and the temperature (T = 20-90 °C) by time-resolved laser fluorescence spectroscopy (TRLFS) and quantum chemical calculations. Four complex species ([Cm(Ox)n]3-2n, n = 1, 2, 3, 4) are identified, and their molar fractions are determined by peak deconvolution of the emission spectra. The conditional log K′n(T) values of the first three complexes are calculated and extrapolated to zero ionic strength with the specific ion interaction theory approach. The [Cm(Ox)4]5- complex forms only at high temperatures. Thus, the log K40(T) value was determined at T > 60 °C. The log K10(25 °C) = 6.86 ± 0.02 decreases by 0.1 logarithmic units in the studied temperature range. The log K20(25 °C) = 4.68 ± 0.09 increases by 0.35, and log K30(25 °C) = 2.11 ± 0.05 increases by 0.37 orders of magnitude. The log Kn0(T) (n = 1, 2, 3) values are linearly correlated with the reciprocal temperature. Thus, their temperature dependencies are fitted with the linear Van’t Hoff equation yielding the standard reaction enthalpy (ΔrHm0) and standard reaction entropy (ΔrSm0) of the stepwise formation of the [Cm(Ox)n]3-2n species (n = 1, 2, 3). Furthermore, the binary ion-ion interaction coefficients of the four Cm(III) oxalate species with Cl-/Na+ are determined. The binding energies, bond lengths, and bond angles of the different Cm(III) oxalate complexes are calculated in the gas phase as well as in a box containing 1000 H2O molecules by ab inito calculations and molecular dynamics simulations, respectively.
Gesehen am 18.06.2020